2009
DOI: 10.1002/eji.200939378
|View full text |Cite
|
Sign up to set email alerts
|

A role for endobrevin/VAMP8 in CTL lytic granule exocytosis

Abstract: CTL clear virus-infected cells and tumorigenic cells by releasing potent cytotoxic enzymes stored in preformed lytic granules. The exocytosis process includes polarization of lytic granules toward the immunological synapse, tethering of lytic granules to the plasma membrane and finally fusion of lytic granules with the plasma membrane to release cytotoxic enzymes. Although much is known about the molecular machineries necessary for the earlier steps in lytic granule exocytosis, the molecular machinery governin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 18 publications
(29 reference statements)
2
40
2
Order By: Relevance
“…In line with this result, it was reported that a knockdown of syntaxin-11 in NK cells reduced their cytotoxic activity, whereas syntaxin-11 overexpression was able to augment cytotoxicity (34). Recently, a reduced exocytosis of lytic granules and an impaired cytotoxic activity of CTL from mice deficient for VAMP8 have been reported (24). We show in this study that Qb-SNARE vti1b is involved in the exocytosis of lytic granules from CTL and confirm this function for the R-SNARE VAMP8.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In line with this result, it was reported that a knockdown of syntaxin-11 in NK cells reduced their cytotoxic activity, whereas syntaxin-11 overexpression was able to augment cytotoxicity (34). Recently, a reduced exocytosis of lytic granules and an impaired cytotoxic activity of CTL from mice deficient for VAMP8 have been reported (24). We show in this study that Qb-SNARE vti1b is involved in the exocytosis of lytic granules from CTL and confirm this function for the R-SNARE VAMP8.…”
Section: Discussionmentioning
confidence: 55%
“…In platelets, VAMP8 is involved in exocytosis of dense granules, a granules, and lysosomes (23). Recently, VAMP8 has also been suggested to be involved in granule exocytosis from CTL (24). In addition, VAMP7 has been reported to be essential for granule exocytosis by a NK cell line (25), but its role in primary killer cells has not been determined.…”
mentioning
confidence: 99%
“…It is possible that there is substantial divergence in the machinery that controls LG exocytosis in mouse and human cells. However, other groups have observed that VAMP8 colocalizes with LG markers, and Vamp8 knockout mice displayed reduced granule exocytosis and defective cytotoxic activity (65,66). Moreover, a recent study proposed that human CTL cytotoxicity depends on VAMP8-mediated recycling of endosomes at the IS (37), although these fusion events may involve a different set of SNAREs such as VTI1a, VTI1b, STX6, or SNAP29 that we identified as VAMP8 binding partners in Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Subsequently it has been shown that VAMP8 is involved in exocytosis in pancreatic acinar cells (16), mast cells (17,18), cytotoxic T lymphocytes (19), platelets (20,21), and kidney collecting duct epithelia (22).…”
mentioning
confidence: 99%